2013
DOI: 10.1590/1982-43272356201312
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction: The Role of Social Skills of Husbands and Wives

Abstract: Among the multiple determinants of marital satisfaction, evidence points to the social skills of married couples. This study investigates the correlations between these constructs, cross-correlating data from husband and wives. A total of 406 married individuals, 188 men and 218 women, completed the Marital Satisfaction Scale, Social Skills Inventory (SSI-Del-Prette) and Marital Social Skills Inventory (MSSI-Villa&Del-Prette). The results revealed a significant correlation among the scores of the three ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
17
0
8
Order By: Relevance
“…Several studies have examined marital satisfaction, each study focused on relevant variables, Some studies emphasized on the importance of love in the occurrence of marital satisfaction such as study Carandang & Guda (2015), Other studies have tested the effect of communication in marital relationships such as study of Abbasi & Afsharinia (2015), The effect of age on marital satisfaction was also discussed in Dabone (2014), One of the variables studied in relation to marital satisfaction was the Rebello et al study (2014), which found an impact on love, partnership, and jealousy in determining the level of marital satisfaction, while the study by Javanmard & Garegozlo (2014) showed the role of some personal factors in marital satisfaction, related variables were Villa & Prette (2013) in Brazil, which dealt with social skills on marital satisfaction, The study of Yadalijamaloye et al (2013) focused on the study of the effect of selfassessment on marital satisfaction, this study sample was large and included only women, Bloch et al (2013) focused on the role of emotional exchange among couples and its impact on the level of marital satisfaction. The study of Zainah et al (2012) also examined the variables of the duration of marriage and income and its impact on levels of marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined marital satisfaction, each study focused on relevant variables, Some studies emphasized on the importance of love in the occurrence of marital satisfaction such as study Carandang & Guda (2015), Other studies have tested the effect of communication in marital relationships such as study of Abbasi & Afsharinia (2015), The effect of age on marital satisfaction was also discussed in Dabone (2014), One of the variables studied in relation to marital satisfaction was the Rebello et al study (2014), which found an impact on love, partnership, and jealousy in determining the level of marital satisfaction, while the study by Javanmard & Garegozlo (2014) showed the role of some personal factors in marital satisfaction, related variables were Villa & Prette (2013) in Brazil, which dealt with social skills on marital satisfaction, The study of Yadalijamaloye et al (2013) focused on the study of the effect of selfassessment on marital satisfaction, this study sample was large and included only women, Bloch et al (2013) focused on the role of emotional exchange among couples and its impact on the level of marital satisfaction. The study of Zainah et al (2012) also examined the variables of the duration of marriage and income and its impact on levels of marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…O THS pode ser considerado um campo em ascensão no Brasil (Del Prette & Del Prette, 2017), tendo aplicabilidade em diversos contextos (e. g. saúde, educação, trabalho/organizações), inclusive nas relações entre parceiros íntimos (Cardoso & Del Prette, 2017;Villa & Del Prette, 2013). Os estudos desenvolvidos sob o referencial do THS têm indicado que um repertório elaborado de habilidades sociais está correlacionado a menor vulnerabilidade a transtornos; relacionamentos saudáveis na família; qualidade de vida; resolução de problemas interpessoais; autoconfiança, otimismo, resiliência; rede de apoio e amigos; bom relacionamento afetivo e conjugal .…”
Section: Habilidades Sociais: Marco Teórico E Contribuições Para As Runclassified
“…No caso desse último, para que uma relação conjugal (aquela que acontece dentro de uma interação afetivo-sexual, e. g. namoro, noivado, união estável, casamento e outras) possa ser benéfica para ambos os parceiros, é necessária uma diversidade de comportamentos sociais que colaborarão para o bem-estar do casal. Esse conjunto de comportamentos que favorece um relacionamento conjugal satisfatório e minimiza os conflitos é chamado de habilidades sociais conjugais (Del Prette & Del Prette, 2014; Villa & Del Prette, 2013).…”
Section: Habilidades Sociais: Marco Teórico E Contribuições Para As Runclassified
“…Foram considerados somente os relatos de pesquisa empírica, que efetivamente utilizaram a ESC na investigação. Foram recuperados oito artigos (Dela Coleta, 1992;Oliveira, Falcone, & Ribas, 2009;Ribeiro, Pinho, & Falcone, 2011;Sardinha, Falcone, & Ferreira, 2009;Sbicigo & Lisboa, 2009;Scorsolini-Comin & Santos, 2011a, 2011bVilla & Del Prette, 2013), os quais revelaram que, após a adaptação da ESC (Dela Coleta, 1989), nenhum estudo de verificação das propriedades psicométricas do instrumento foi realizado.…”
unclassified